KREATIVITAS GURU PAI DALAM MENINGKATKAN KEMAMPUAN BACA TULIS AL-QUR’AN DI SD AL- ITTIHADIYAH LAUT DENDANG: Islamic education - Maulana, M Zikri; Nahar, Syamsu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstract This research aims to examine the creativity of Islamic Religious Education (PAI) teachers in improving students' Al-Qur'an literacy skills at SD Al-Ittihadiyah Laut Dendang. The main focus of this study is to uncover the forms of creativity implemented by teachers in the Al-Qur'an literacy learning process, the application and implications of the creativity used, and its impact on enhancing students' Al-Qur'an literacy skills. The background of this research stems from the reality that many elementary school students still struggle to read and write the Al-Qur'an correctly, coupled with a lack of innovation in the learning process carried out by PAI teachers.This study uses a descriptive qualitative approach with data collection techniques including observation, in-depth interviews with PAI teachers, the school principal, and students, as well as documentation of Al-Qur'an literacy learning activities. The data were analyzed using a data reduction, data display, and conclusion-drawing approach to obtain a comprehensive overview of teacher creativity in Al-Qur'an literacy learning. The research findings indicate that PAI teachers at SD Al-Ittihadiyah Laut Dendang have developed various creative methods in Qur'an literacy instruction, such as utilizing audio-visual media, implementing educational games based on hijaiyah letters, providing adaptive learning differentiation, and offering simple rewards as motivation.. The implementation of these creative methods—ranging from word-building, singing, group formation, to giving prizes as motivation—has a significant impact on increasing students' interest in learning, active engagement in the learning process, and mastery of the competence to read the Al-Qur'an with tartil and write Arabic letters correctly. Furthermore, teacher creativity not only affects students' cognitive aspects but also strengthens their affective and spiritual dimensions. These results indicate that teacher creativity is a key element in the success of Islamic religious education at the basic level. Therefore, improving the capacity and training of teachers in pedagogical creativity becomes an important input for educational institutions to address the challenge of low Al-Qur'an literacy among elementary school students.